Trois regards sur le mouvement des « Gilets jaunes » - Olivier Fillieule; Samuel Hayat; Sylvie Monchatre (La Nouvelle Revue du Travail)
The so-called Yellow Jackets movement – enigmatic is many ways – has been a topic of numerous political, media and sociological interpretations. Sociologists with an interest in work matters and/or social movements have been particularly intrigued by this movement, notably by the ostensible disinterest in work issues and absence of employer interaction. From a labour movement perspective, the consensualist orientation and activists’ refusal to designate representatives have also been interesting. All researchers are having to ask themselves again age-old questions about how they engage with social conflict and when it is suitable for them to publicise their interpretations. Three researchers, specialists in labour and in social conflicts, have studied the movement and debate it in this article.